Monetary Policy Predictability in the Euro Area: An International Comparison - Bjørn-Roger Wilhelmsen; Andrea Zaghini (Norges Bank, 2005)
The paper evaluates the ability of market participants to anticipate monetary policy decisions in the euro area and in 13 other countries. First, by looking at the magnitude and the volatility of the changes in the money market rates we show that the days of policy meetings are special days for financial markets. Second, we find that the predictability of the ECB's monetary policy is fully comparable (and sometimes slightly better) to that of the FED and the Bank of England. Finally, an econometric analysis of the ability of market participants to incorporate in the current money rates the expected changes in the key policy rate shows that in the euro area policy decisions are anticipated well in advance.
hdl:11250/2498426
Keywords: E4; E5; G1; 330; monetary policy; predictability; money market rates